2001
DOI: 10.1046/j.1523-1747.2001.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

The Paracrine Role of Stem Cell Factor/c-kit Signaling in the Activation of Human Melanocytes in Ultraviolet-B-Induced Pigmentation

Abstract: The interaction of stem cell factor with its receptor, c-kit, is well known to be critical to the survival of melanocytes. Little is known about the role(s) of the stem cell factor/c-kit interaction in epidermal pigmentation, however. To clarify whether the stem cell factor/c-kit signaling has a paracrine role in ultraviolet-B-induced pigmentation, we determined whether the exposure of human keratinocytes, melanocytes, and the epidermis to ultraviolet B light stimulates the expression of stem cell factor or c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
194
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 180 publications
(206 citation statements)
references
References 48 publications
(58 reference statements)
8
194
4
Order By: Relevance
“…47,48 Further, SCF production by keratinocytes is increased by ultraviolet B (UVB) radiation, which is known to increase nevi size and number. 49,50 In the same line, transgenic mice expressing elevated levels of SCF develop melanocyte dysplasia. 51 Thus, SCF by preventing apoptosis in melanocytes could favor melanocyte growth and transformation.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Further, SCF production by keratinocytes is increased by ultraviolet B (UVB) radiation, which is known to increase nevi size and number. 49,50 In the same line, transgenic mice expressing elevated levels of SCF develop melanocyte dysplasia. 51 Thus, SCF by preventing apoptosis in melanocytes could favor melanocyte growth and transformation.…”
Section: Discussionmentioning
confidence: 99%
“…1). SCF and bFGF are wellknown melanogenic paracrine factors, especially with respect to responses to UV exposure (Grichnik et al, 1998;Hachiya et al, 2001), but neither of them showed different expression patterns in the various skin types. DKK1 is a paracrine factor responsible for topographical differences of skin color in palm versus trunk skin (Yamaguchi et al, 2004), but although there was quite a variation in expression patterns of DKK1 and the related DKK3, neither of those showed expression patterns that consistently correlated with skin phototype.…”
Section: Expression Of Known Fibroblast-derived Melanogenic Paracrinementioning
confidence: 99%
“…However of interest, is the relationship of stem cell factor/c-kit to melanocytes, and has been implicated in the proliferation, survival, and migration of embryonic melanoblasts. [20][21] Furthermore, fibroblastic tumor cell-derived stem cell factor may play an important role in melanocyte hyperplasia and hyperpigmentation in dermatofibromas. 13 Utilizing c-kit (CD 117) immunostaining we did note significant staining of dermatofibromas vs the adjacent nonlesional dermis, similar to a previous study.…”
Section: Histologic Findingsmentioning
confidence: 99%